Leveragıng Technology for Influencıng Consumer Decısıon-Makıng Process ın the Indıan Real-Estate Landscape - Prateek Dubey (International Journal of Advanced Science and Technology, 2020)
The rapid advancement in the fields of Augmented reality and Virtual reality has opened up a plethora of opportunities to be implemented in the Indian Real Estate scenario. This paper investigates the scope of Virtual Reality beyond the design and feel of the property and aims at providing an immersive experience of how the entire ecosystem of a project will look once it is completed. This paper also studies the effect of incorporating Mixed Reality in the consumer decision making journey. The implementation of Mixed Reality is certainly a game-changer in the real estate scenario, affecting both the buyer and seller in terms of saving time and money. This paper analyses the effect of the virtual environment on the consumer decision-making process. The paper aims to gather responses from the potential buyers of real estate in the near future and determine what factors are taken into account while influencing their decision to purchase a property and how big a share Virtual Reality has in that. VR has successfully enabled the real estate industry to leverage technology in giving the customers an immersive experience. It has opened the doors for firms to construct a 3-D view of homes thereby making it possible for the potential buyers around the world to feel as though they were actually viewing a property physically.